he Impact of Technology upon Formal Communication: Texting Impacting the Standard English - NAZIA SULEMAN; UZMA SADIQ; SAFIA SIDDIQUI (Journal of Business & Tourism, 2021)
With the invention of mobile phones text messaging has become a popular medium of communication. Its users are multiplying with every passing day. Its use is not only limited to informal but to formal communication as well. Students are the advent users of mobile phones and of SMS as well. The present study manifests the fact that students are practicing SMS for a number of reasons and a good amount of time is spent upon it which is resulting in typographical features, graphones and rebus writing. Data is collected through questionnaires and came to the conclusion that its effect is obvious in the L2 users in general and examinations in particular.